ANÁLISE BIBLIOMÉTRICA SOBRE POLÍTICAS PÚBLICAS - Fabio Freitas da Silva (Universidade Federal do Maranhão, 2019)
This work aims at showing the evolution of the public policy theme in a national and worldwide context by means of a bibliometric analysis. More general indicators on the global assessment were proposed, such as the timeline of publications and countries that most debate the theme; while in the Brazilian conjuncture, more specific indicators were generated, such as the partnership network between Brazil and other countries and institutions. The main results showed that the first publication in the world about the theme under study was in 1909, while in Brazil it was in 1987. They also demonstrated that the United States stood out relating to the number of publications. Another question was that, despite the late development of the area of public policies, Brazil ranks fourth worldwide. Regarding institutions, Universidade de São Paulo-USP (Sao Paulo University) concentrates the largest amount of published works, however, the United States stands out as a whole.